Analisis Faktor-faktor Penghambat Knowledge Tranfer (Studi Pada PT Jasatama Polamedia Cabang Yogyakarta) - , Dimas Priyandana Utama ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Knowledge has become one of the important strengths in promoting the success of the business, which is an intangible asset in making differentiation to gain competitive advantage. So when an organization or employee identifies important knowledge, then they can make the process of knowledge transfer to benefit the organization's advantage. However, the knowledge transfer process does not always run smoothly, and there are several factors that inhibit the process. This study aims to identify factors inhibiting the transfer of knowledge in the application of SOP on the supervisor service points in PT Jasatama Polamedia Yogyakarta branch. The supervisor service points are less likely to understand the application of SOP to the maximum so frequent repetition of mistakes, ineffective operations results to emergence of losses for the company. In fact, SOP role is supporting the achievement of the mission and goals of the company, and is able to create a professional culture within the organization. This research is a qualitative descriptive study. Data were obtained through interviews with the Area Manager and Branch Manager as a source of knowledge as well as three staff supervisor of service points as recipients of knowledge. The results showed there were four factors inhibiting the transfer of knowledge in the application of SOP on the supervisor service points in PT Jasatama Polamedia Yogyakarta branch. Limiting factors are the barren organizational context, lack of close relationship, lack of motivation and lack of retentive capacity.